bring the a's to one side... u then get 9a = 27 ... divide and answer is a = 3
2006-11-08 11:39:21
·
answer #1
·
answered by greg95616 2
·
0⤊
0⤋
7a + 10 = -2a + 37 Collect like terms. Knowns on the right
7a +2a + 10 -10 = -2a + 2a + 37 - 10 unknowns on the left
9a = 27 Divide both sides of the equation by 9
a = 3
2006-11-08 12:01:35
·
answer #2
·
answered by Max 6
·
0⤊
0⤋
7a +10 = -2a +37
7a +2a = 37 -10
9a = 27
a = 3
Verification: 7(3) +10 =? -2(3) + 37
21 + 10 =? -6 +37
31 = 31 (True)
2006-11-08 11:41:46
·
answer #3
·
answered by frank 7
·
0⤊
0⤋
first bring all the a's to one side (preferrably the left) and the numbers to the other side:
=> 7a + 2a = 37 - 10 (remember that the signs change when moved across the =)
=> 9a = 27 (to solve for a divide both sides by 9)
=> a = 27/9 = 3
2006-11-08 11:42:24
·
answer #4
·
answered by Lisa T 1
·
0⤊
0⤋
You have the start.
First take the two over to make 7a + 2a + 10 = 37.
Then you have 9a + 10 = 37.
Then move the 10 over to make 9a = 37 - 10.
Then you have 9a = 27.
then divide both sides by 9 to get 9a/9 = 27/9.
Complete the division to get a=3.
2006-11-08 11:41:42
·
answer #5
·
answered by nhzero 3
·
0⤊
0⤋
a = 3
2006-11-08 11:46:11
·
answer #6
·
answered by Mark Antony 3
·
0⤊
0⤋
7a + 10 = -2a + 37
+2a +2a
9a + 10 = 37
+-10 +-10
9a=27
9a/9=27/9
a=3
2006-11-08 11:42:52
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
7a+10= -2a+37
+2a +2a
9a+10=37
-10 -10
9a=27
/9 /9
a=3
2006-11-08 11:40:51
·
answer #8
·
answered by justme 6
·
0⤊
0⤋
7a +10= -2a+37 or
7a+2a=37-10 or
9a=27 or
a=27/9
a= 3
2006-11-08 11:42:06
·
answer #9
·
answered by Zacky 2
·
0⤊
0⤋
7a + 10 = -2a + 37
-10 to both sides
7a = -2a +27
+2a to both sides
9a = 27
divide by 9 on both sides
a = 3
2006-11-08 11:39:59
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋
sure :)
Step 1: combine like terms (already done... no multiple "a" or constants on one side of the = )
Step 2: isolate the variables on one side, and constants on the other side of the =
7a - (-2a) + 10 = -2a - (-2a) + 37
7a + 2a + 10 = 37
9a + 10 = 37
9a + 10 - 10 = 37 - 10
9a = 27
Step 3: solve!
9a / 9 = 27 / 9
a = 3
:)
Hope this helps!
2006-11-08 11:39:04
·
answer #11
·
answered by disposable_hero_too 6
·
0⤊
0⤋